The Development of a Coding Scheme for Intergenerational Learning and Its Application to the Patterns of Intergenerational Collaborative Communication - Wang, Ya-Ling (Frontiers in Psychology, 2021)
Much research has focused on intergenerational learning. However, its patterns and processes have rarely been explored. Therefore, this study aimed to develop a coding scheme for intergenerational learning, and to explore the patterns of collaborative communication emerging in the context of intergenerational learning. A total of 16 individuals (7 older adults and 9 university students) participated in the study. Participants were invited to design digital games with their intergenerational team members. Of all the interactions, two sets of collaborative interactions were coded and analyzed. The findings revealed that the coding scheme for intergenerational learning was developed with high inter-rater reliability for three sub-systems: power process, communication skills, and responses to bids. Additionally, although the patterns of collaborative communication showed a balance of power during the task involving the collection of game elements, younger learners dominated during the task of completing the game prototype.